Kirsten Ry kind-Eriksen: Smag og stil. Juveler og sølvvarefabrikant V. Christesen 1850-1900. (Det Danske Kunstindustrimuseum, 1991). 46 s., 60 kr. - Vedel-Smith, Henrik (Historie/Jyske Samlinger, 1994)
-